2011
DOI: 10.1038/nri2998
|View full text |Cite
|
Sign up to set email alerts
|

Expanding TRAF function: TRAF3 as a tri-faced immune regulator

Abstract: Tumour necrosis factor receptor (TNFR)-associated factor (TRAF) proteins are essential components of signalling pathways activated by TNFR or Toll-like receptor (TLR) family members. Acting alone or in combination, the seven known TRAFs control many biological processes, including cytokine production and cell survival. The function of one TRAF in particular, TRAF3, remained elusive for many years. Recent work has revealed that TRAF3 is a highly versatile regulator that positively controls type I interferon pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
461
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(472 citation statements)
references
References 93 publications
8
461
1
2
Order By: Relevance
“…Components of the free-radicalgenerating machinery were not the only factors that were targeted by Rv1988. TRAF3, the TNF receptor-associated factor, plays an important role in both B-cell and T-cell dependent immune response 39 . The histone H3-arginine methylation-dependent transcriptional repression of TRAF3 in Rv1988::M. smegmatisinfected THP1 cells indicated that mycobacteria uses Rv1988 to target specific genes important in mounting an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Components of the free-radicalgenerating machinery were not the only factors that were targeted by Rv1988. TRAF3, the TNF receptor-associated factor, plays an important role in both B-cell and T-cell dependent immune response 39 . The histone H3-arginine methylation-dependent transcriptional repression of TRAF3 in Rv1988::M. smegmatisinfected THP1 cells indicated that mycobacteria uses Rv1988 to target specific genes important in mounting an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Activation of ERK1/2 proceeds TBK1 and IKKε then mediate phosphorylation of IRF3. 55,56 Consequently, cells deficient in TRAF3, TBK1 or IKKε are severely compromised in their ability to activate IRF3 and induce IFNβ upon TLR3 stimulation. 53,[55][56][57][58] PI3K.…”
Section: Pathways Of Activation By Toll-like Receptorsmentioning
confidence: 99%
“…55,56 Consequently, cells deficient in TRAF3, TBK1 or IKKε are severely compromised in their ability to activate IRF3 and induce IFNβ upon TLR3 stimulation. 53,[55][56][57][58] PI3K. Phosphoinositide 3-kinases (PI3K) are a family of lipid kinases consisting of three classes (class I, class II and class III) based upon substrate specificity as well as several structural characteristics.…”
Section: Pathways Of Activation By Toll-like Receptorsmentioning
confidence: 99%
“…Ligand binding to IL-1R1 stimulates recruitment of the IL-1 receptor accessory protein, IL-1RAcP, which is necessary for IL-1 signalling. There is significant commonality between TLR and IL-1R1 signalling [30]. Upon activation, both TLR and IL-1R1 receptor complexes recruit specific adaptor proteins (e.g.…”
Section: Damp Receptors and Cardiac Remodellingmentioning
confidence: 99%